Antistatic talcum powder and graphene composite reinforced material and in-situ polymerization process thereof

By employing an in-situ polymerization process of antistatic talc powder and functionalized graphene composite material, the problems of static accumulation and poor dispersibility of talc powder were solved, achieving high-efficiency antistatic properties and excellent mechanical properties of the material.

CN120966133APending Publication Date: 2025-11-18LIAONING AIHAI TALC CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202511132823.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-13
Publication Date
2025-11-18

AI Technical Summary

Technical Problem

In existing technologies, talc powder is prone to static electricity accumulation and has poor dispersibility. Adding graphene is costly and can easily lead to a decrease in interfacial compatibility. In traditional mechanical blending processes, talc powder has a large particle size, graphene is prone to agglomeration, and the antistatic agent has insufficient durability.

Method used

An antistatic talc powder and functionalized graphene composite material was used, which was modified by in-situ polymerization. The talc powder was refined by ball milling using a silane coupling agent. The graphene was ultrasonically dispersed in deionized water, and an ionic liquid was added as an antistatic synergist to form a conductive network and improve the interfacial bonding force.

Benefits of technology

It effectively reduces the surface resistance of materials, enhances the flexural modulus, prevents filler agglomeration, extends the service life of materials, and improves interfacial bonding and dispersibility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120966133A_ABST
    Figure CN120966133A_ABST
Patent Text Reader

Abstract

The invention provides an antistatic talcum powder and graphene composite reinforced material and an in-situ polymerization process thereof, and belongs to the technical field of polymer composite materials. According to the antistatic talcum powder and graphene composite reinforced material and the in-situ polymerization process thereof, the antistatic talcum powder and graphene composite reinforced material is prepared from the following raw materials in parts by weight: 100 parts of matrix resin, 5-30 parts of modified talcum powder, 0.5-5 parts of functionalized graphene and 0.1-2 parts of an antistatic synergist, the modified talcum powder is subjected to surface treatment by a silane coupling agent, the particle size range is 1-10 [mu] m, and the functionalized graphene is graphene oxide or reduced graphene oxide. Through the synergistic effect of the silane coupling agent modified talcum powder and the functionalized graphene and in combination with the ionic liquid antistatic agent, the surface resistance of the material is remarkably reduced. Nanoscale dispersion is realized by adopting an in-situ polymerization process, and the method is suitable for the field of high-performance engineering plastics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer composite materials technology, and more specifically, to an antistatic talc-graphene composite reinforcing material and its in-situ polymerization process. Background Technology

[0002] While talc powder, as a traditional filler, can improve the mechanical properties of materials, it also has problems such as easy static electricity accumulation and poor dispersibility. Adding graphene alone to modify materials is costly, and excessive addition can easily lead to a decrease in interfacial compatibility.

[0003] While some publicly available materials mention graphene and talc composite fillers, they do not solve the static electricity problem. Although some products are coated with antistatic agents, they suffer from insufficient durability. Furthermore, in traditional mechanical blending processes, the dispersed particle size of talc is usually >20μm, and graphene is prone to π-π stacking to form agglomerates >500nm. The half-life of the antistatic agent coated on the surface is only 30-60 days. Summary of the Invention

[0004] To overcome the above deficiencies, the present invention provides an antistatic talc-graphene composite reinforcing material and its in-situ polymerization process to overcome or at least partially solve the above technical problems.

[0005] This invention is implemented as follows:

[0006] This invention provides an antistatic talc-graphene composite reinforced material and its in-situ polymerization process, comprising the following raw materials in parts by weight:

[0007] The matrix resin comprises 100 parts by weight, modified talc powder comprises 5-30 parts by weight, functionalized graphene comprises 0.5-5 parts by weight, and antistatic synergist comprises 0.1-2 parts by weight.

[0008] In a preferred embodiment, the matrix resin is polypropylene, polyamide, or polycarbonate.

[0009] In a preferred embodiment, the modified talc powder is surface-treated with a silane coupling agent, and the particle size range is 1-10 μm.

[0010] In a preferred embodiment, the functionalized graphene is graphene oxide or reduced graphene oxide, with a specific surface area of ​​200-800 m². 2 / g, wherein the antistatic synergist is an ionic liquid.

[0011] In a preferred embodiment, the talc powder is first ball-milled and then reacted with γ-aminopropyltriethoxysilane in an ethanol solution for 2-4 hours at a temperature of 60-80°C.

[0012] In a preferred embodiment, the talc powder is ball-milled using a planetary ball mill with a ball-to-material ratio of 5:1 to 8:1, a rotation speed of 250 to 350 rpm, and a time of 0.5 to 1.5 hours.

[0013] In a preferred embodiment, the graphene is dispersed in deionized water, polyvinylpyrrolidone is added, and the mixture is ultrasonically treated for 30-60 minutes.

[0014] In a preferred embodiment, the graphene is dispersed using a probe-type ultrasonic instrument in pulse mode with a power of 600W.

[0015] In a preferred embodiment, including,

[0016] S1; The modified talc powder, functionalized graphene and monomer are premixed in proportion, and an initiator is added, wherein the monomer is preferably acrylate or styrene, and the initiator is preferably potassium persulfate;

[0017] S2; Under nitrogen protection, stir for 3-6 hours at a temperature of 70-90℃ to form a prepolymer;

[0018] S3; The prepolymer and matrix resin are melt-blended and then extruded and granulated.

[0019] In a preferred embodiment, the modified talc, functionalized graphene, and monomer are stirred in a closed reactor with an anchor stirrer, wherein the stirring rate is 200-300 rpm and the nitrogen flow rate is 0.5 L / min.

[0020] This invention provides an antistatic talc-graphene composite reinforced material and its in-situ polymerization process, the beneficial effects of which include:

[0021] 1. Through the synergistic effect of talc and graphene, graphene constructs a conductive network to reduce surface resistance, while talc increases flexural modulus. This in-situ polymerization process can enhance interfacial bonding and prevent filler agglomeration. Furthermore, the use of ionic liquid as an antistatic synergist can effectively extend the service life of the material. Attached Figure Description

[0022] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation of the scope. For those skilled in the art, other related drawings can be obtained from these drawings without creative effort.

[0023] Figure 1 This is a process flow diagram of the preparation of composite materials provided by an embodiment of the present invention;

[0024] Figure 2 The dispersion morphology of graphene and talc in the matrix is ​​provided for the embodiments of the present invention. Detailed Implementation

[0025] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0026] This invention provides a technical solution: an antistatic talc-graphene composite reinforced material, comprising the following raw materials in parts by weight: 100 parts by weight of matrix resin, 5-30 parts by weight of modified talc, 0.5-5 parts by weight of functionalized graphene, and 0.1-2 parts by weight of antistatic synergist. The matrix resin is polypropylene, polyamide, or polycarbonate. The modified talc is surface-treated with a silane coupling agent and has a particle size range of 1-10 μm. The functionalized graphene is graphene oxide or reduced graphene oxide with a specific surface area of ​​200-800 m². 2 / g, characterized in that the antistatic synergist is an ionic liquid, preferably 1-butyl-3-methylimidazolium hexafluorophosphate, the talc powder is first refined by ball milling, reacted with γ-aminopropyltriethoxysilane in ethanol solution for 2-4 hours at a temperature of 60-80℃, the talc powder is ball-milled by a planetary ball mill with a ball-to-material ratio of 5:1-8:1, a rotation speed of 250-350 rpm, and a time of 0.5-1.5h, the graphene is dispersed in deionized water, polyvinylpyrrolidone is added and ultrasonic treatment is performed for 30-60 minutes, the graphene is dispersed by a probe-type ultrasonic instrument in pulse mode with a power of 600W;

[0027] S1; The modified talc powder, functionalized graphene and monomer are premixed in proportion, and an initiator is added, wherein the monomer is preferably acrylate or styrene, and the initiator is preferably potassium persulfate;

[0028] S2; Under nitrogen protection, stir for 3-6 hours at a temperature of 70-90℃ to form a prepolymer;

[0029] S3; The prepolymer and matrix resin are melt-blended and then extruded and granulated.

[0030] The modified talc powder, functionalized graphene, and monomers are stirred in a closed reactor with an anchor stirrer at a stirring rate of 200-300 rpm and a nitrogen flow rate of 0.5 L / min.

[0031] First Embodiment

[0032] Talc ore is crushed to a particle size ≤5mm using a jaw crusher. Carbonate impurities are removed by an air classifier to obtain primary talc powder. This primary talc powder is then added to an air jet mill and pulverized before being sieved through a 200-mesh sieve to obtain ultrafine talc powder. 2000g (20 parts) of the ultrafine talc powder is taken and mixed with 40g of KH550 silane coupling agent and 4L of anhydrous ethanol (99.7% purity). The mixture is then transferred to a planetary ball mill. Preferably, in this embodiment, the planetary ball mill uses zirconia ball milling media. The milling speed is set to 280rpm, and the mixture is ball-milled in a 70℃ water bath for 3 hours (reversing the direction every 30 minutes). After the reaction, the mixture is filtered, washed three times with ethanol, and vacuum-dried at 80℃ for 5 hours to obtain KH550 modified talc powder. Graphene oxide is then added to the mixture. 15g of PVP was added to 500mL of deionized water and 3g of PVP. A probe-type ultrasonic instrument was used, preferably with an ultrasonic probe diameter of 6mm in this embodiment, to obtain a PVP-modified graphene oxide dispersion. Modified talc powder (20 parts), PVP-modified graphene oxide dispersion, 1000g of PP resin (100 parts), and ionic liquid (0.5 parts) were added to a high-speed mixer to obtain a premix. The premix was added to a twin-screw extruder, and the extrudate was water-cooled (water temperature 25℃) and pelletized (particle size 3mm×4mm) to obtain composite material masterbatch. The masterbatch was added to a fluidized bed dryer to reduce the moisture content to 0.08%. Then, it was passed through a vibrating screen to remove fine powder <0.5mm to obtain qualified masterbatch, which was then injection molded using an injection molding machine.

[0033] Tests showed that the surface resistivity of the antistatic talc-graphene composite reinforced material obtained through this process was 3.2 × 10⁻⁶. 5 Ωcm, tensile strength 48MPa, flexural modulus: 3.5GPa.

[0034] Second Embodiment

[0035] Following the steps of the first embodiment above, 1500g (15 parts) of modified talc powder was obtained, 20g (2 parts) of reduced graphene oxide was taken, and 500mL of N,N-dimethylformamide (DMF) was added. The mixture was ultrasonically dispersed for 30min to obtain an rGO dispersion. 15 parts of modified talc powder, 2 parts of rGO dispersion, and 100 parts of methyl methacrylate monomer were added to a reaction vessel. The stirring blades were designed as a three-layer inclined blade type, and the stirring speed was 200rpm. The reaction vessel was first evacuated to -0.095MPa, and then purged with nitrogen to a slightly positive pressure (0.02MPa). After 3 cycles, the temperature was raised to 75℃, and 0.5 parts of initiator benzoyl peroxide were added. Preferably, in this embodiment, the initiator was added dropwise. The reaction was kept at the temperature for 4h to obtain a prepolymer. The prepolymer, 100 parts of PC resin, and 0.8 parts of ionic liquid were added to a twin-screw extruder, extruded and granulated, and then injection molded by an injection molding machine.

[0036] Tests showed that the surface resistivity of the antistatic talc-graphene composite reinforced material obtained through this process was 8.7 × 10⁻⁶. 4 Ωcm, notched impact strength is 15kJ / m 2 Its bending strength is 95 MPa.

[0037] Third Embodiment

[0038] Take 100 parts of matrix resin, 35 parts of modified talc, 35 parts of functionalized graphene (preferably reduced graphene oxide), 1.2 parts of antistatic synergist (preferably 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt), and 8 parts of plasticizer (preferably dioctyl phthalate). When ball milling the talc, add 0.5 parts of calcium stearate as a lubricant to prevent agglomeration caused by high filling. When dispersing the graphene, premix the reduced graphene oxide and the plasticizer dioctyl phthalate and stir at 60°C for 1 hour to form a pregel dispersion. In this embodiment, the temperature zone of the twin-screw extruder is adjusted to 160°C→170°C→165°C→155°C, and the screw speed is reduced to 180 rpm to reduce shear heat.

[0039] Tests showed that the surface resistivity of the antistatic talc-graphene composite reinforced material obtained through this process was 6.4 × 10⁻⁶. 6 Ωcm, notched impact strength is 22kJ / m 2 Its thermal stability is based on an initial decomposition temperature of 248℃.

[0040] Fourth embodiment

[0041] This embodiment employs an in-situ polymerization process of ε-caprolactam monomer. The resulting PA6 resin serves as the matrix for the composite material. The composition includes 25 parts modified talc, 3 parts functionalized graphene (preferably graphene oxide), 0.3 parts antistatic synergist (preferably 1-hexyl-3-methylimidazolium tetrafluoroborate), and 0.5 parts catalyst (preferably sodium caprolactam). Graphene oxide, talc, ionic liquid, and caprolactam monomer are mixed at 60°C and ultrasonically dispersed for 20 min. After adding the catalyst, the mixture is reacted at 90°C (lower than the conventional PA6 polymerization temperature) for 4 h to directly generate the composite material. The reaction product is washed with water and vacuum dried, eliminating the need for melt extrusion.

[0042] Tests showed that the surface resistivity of the antistatic talc-graphene composite reinforced material obtained through this process was 1.2 × 10⁻⁶. 5 It has a tensile strength of 78 MPa and a water absorption rate of 1.8%.

[0043] Fifth Embodiment

[0044] Take 100 parts of matrix resin (preferably recycled polypropylene in this embodiment), 15 parts of modified talc powder, 0.8 parts of functionalized graphene (preferably unoxidized graphene nanosheets in this embodiment), 0.5 parts of antistatic synergist (preferably 1-butyl-3-methylimidazolium tetrafluoroborate in this embodiment), and 5 parts of compatibilizer (preferably maleic anhydride grafted in this embodiment). When ball milling the talc powder, add 0.2 parts of titanate coupling agent NDZ-201 to enhance the interfacial bonding with recycled polypropylene. When blending, first premix the graphene nanosheets, ionic liquid, and maleic anhydride graft in a mixer at 160°C for 5 minutes, then add the talc powder and recycled polypropylene. After extrusion granulation, it is hot-pressed at a pressure of 10 MPa and a temperature of 185°C.

[0045] Tests showed that the surface resistivity of the antistatic talc-graphene composite reinforced material obtained through this process was 2.1 × 10⁻⁶. 7 The Ωcm, flexural modulus is 2.8 GPa, and melt flow rate is 4.2 g / 10 min.

[0046] Sixth Embodiment

[0047] Take 100 parts of matrix resin (preferably polyphenylene ether in this embodiment), 20 parts of modified talc powder (the ball milling process is the same as in the fifth embodiment), 1.2 parts of functionalized graphene, 0.6 parts of antistatic synergist (preferably 1-ethyl-3-methylimidazolium dicyandiamide salt in this embodiment), and 8 parts of compatibilizer (preferably styrene-maleic anhydride copolymer in this embodiment). During the graphene pretreatment, the nitrogen-doped graphene and styrene-maleic anhydride copolymer are refluxed in chloroform for 2 hours to form a pre-coated composite. The pre-coated composite and the antistatic synergist are mixed in a mixer at 220°C for 5 minutes. After that, talc powder and polyphenylene ether are added. The screw speed is 150 rpm. After the extrusion granulation process, the mixture is vulcanized in hot air at 180°C for 30 minutes to promote the stability of the ionic liquid network.

[0048] Tests showed that the surface resistivity of the antistatic talc-graphene composite reinforced material obtained through this process was 4.5 × 10⁻⁶. 6 Ωcm, heat distortion temperature is 158℃, and dielectric constant is 3.2.

[0049] Seventh Embodiment

[0050] Take 100 parts of matrix resin (preferably styrene-ethylene-butene-styrene block copolymer in this embodiment), 10 parts of modified talc, 0.5 parts of functional graphene (preferably carboxylated graphene in this embodiment), 0.3 parts of antistatic synergist (preferably choline phosphate in this embodiment), and 25 parts of plasticizer. Stir the talc with dimethyl silicone oil at 80°C for 1 hour to form a hydrophobic surface. Dissolve the carboxylated graphene and choline phosphate in tetrahydrofuran and mix with the styrene-ethylene-butene-styrene block copolymer solution. Sonicate for 30 minutes. After evaporating the solution, perform a two-roll milling process at a temperature controlled at 60°C to avoid damaging the choline structure at high temperatures. After completion, add 0.1 parts of dicumyl peroxide and selectively crosslink the rubber phase of the styrene-ethylene-butene-styrene block copolymer on a two-roll mill.

[0051] Tests showed that the surface resistivity of the antistatic talc-graphene composite reinforced material obtained through this process was 1.2 × 10⁻⁶. 8 Ωcm, elongation at break 620%, cytotoxicity grade 0 (non-toxic).

Claims

1. An antistatic talc-graphene composite reinforced material, characterized in that: The raw materials include the following parts by weight: The matrix resin comprises 100 parts by weight, modified talc powder comprises 5-30 parts by weight, functionalized graphene comprises 0.5-5 parts by weight, and antistatic synergist comprises 0.1-2 parts by weight.

2. The in-situ polymerization process of the antistatic talc-graphene composite reinforced material according to claim 1, characterized in that, The matrix resin is polypropylene, polyamide, or polycarbonate.

3. The in-situ polymerization process of the antistatic talc-graphene composite reinforced material according to claim 2, characterized in that, The modified talc powder is surface-treated with a silane coupling agent, and its particle size ranges from 1 to 10 μm.

4. The in-situ polymerization process of the antistatic talc-graphene composite reinforced material according to claim 3, characterized in that, The functionalized graphene is graphene oxide or reduced graphene oxide, with a specific surface area of ​​200-800 m². 2 / g, wherein the antistatic synergist is an ionic liquid.

5. The in-situ polymerization process of the antistatic talc powder and graphene composite reinforced material according to claim 4, wherein the talc powder is first refined by ball milling, and then reacted with γ-aminopropyltriethoxysilane in an ethanol solution for 2-4 hours at a temperature of 60-80℃.

6. The in-situ polymerization process of the antistatic talc-graphene composite reinforced material according to claim 5, characterized in that, The talc powder is ball-milled using a planetary ball mill with a ball-to-material ratio of 5:1 to 8:1, a rotation speed of 250 to 350 rpm, and a grinding time of 0.5 to 1.5 hours.

7. The in-situ polymerization process of the antistatic talc-graphene composite reinforced material according to claim 6, characterized in that, The graphene is dispersed in deionized water, polyvinylpyrrolidone is added, and the mixture is ultrasonically treated for 30-60 minutes.

8. The in-situ polymerization process of the antistatic talc-graphene composite reinforced material according to claim 7, characterized in that, The graphene was dispersed using a probe-type ultrasonic instrument in pulse mode with a power of 600W.

9. The in-situ polymerization process of an antistatic talc-graphene composite reinforced material according to claim 8, characterized in that, include, S1; The modified talc powder, functionalized graphene and monomer are premixed in proportion, and an initiator is added, wherein the monomer is preferably acrylate or styrene, and the initiator is preferably potassium persulfate; S2; Under nitrogen protection, stir for 3-6 hours at a temperature of 70-90℃ to form a prepolymer; S3; The prepolymer and matrix resin are melt-blended and then extruded and granulated.

10. The in-situ polymerization process of an antistatic talc-graphene composite reinforced material according to claim 9, characterized in that, The modified talc powder, functionalized graphene, and monomers are stirred in a closed reactor with an anchor stirrer at a stirring rate of 200-300 rpm and a nitrogen flow rate of 0.5 L / min.

Citation Information

Cited By

  • Graphene modified antistatic highlight powder coating and preparation method thereof

    CN121537857A

  • A graphene-modified antistatic high-gloss powder coating and its preparation method

    CN121537857B